Atividades para o estudo das Medidas de Tendência Central: uma proposta com o apoio do GeoGebra - Araújo, José Ronaldo Alves (2018)
This dissertation presents a qualitative investigation which was carried out within thscope of Statistics teaching and lasted for the potentialities of GeoGebra for an understanding of the Meditation of Central Tendency concepts. Based on the didactic actions, the formulation, validation and institutionalization of the Theory of Didactic Situations, the search was developed through a sequence of activities. The methodological methods for the elaboration, application and analysis of the activities were realized by the Engineering dimensions as preliminary techniques such as a priori analysis, experiment and a posteriori analysis. The participants in the research program was a high school group of the 1st grade in a public school in the state of São Paulo. The application of the class was carried out in a computer lab of the same school and was divided by four sessions of five minutes. The participants, through GeoGebra, treated the data of each activity and were answering the questions of the present study. Ahead of questions and answers, it was possible to identify, from the dialectical practices of the theoretical, the potentialities of GeoGebra for an understanding of the proposed mathematical objectives, such as, in a dialectic of action, the organization of the data and the search for answers to some questions. This organization of the data in tables, lists, ordered lists, graphical representation or even values for the Central Administration classes allows the students, a formulation dialectic, to reflect on the representation of the values in relation to the data set. The various representations of the data in the GeoGebra windows, in a validation dialectic, favor the participation of the participants on the relation of the indicators with the data of their origin. These multiple representations of a set of data allow other questions, allowing the discussion on market conditions, such as the evaluation of trends, which contributed to the teacher, a dialectic of institutionalization with the students, would be able to promote of consolidation of knowledge